2016
DOI: 10.1038/bcj.2016.61
|View full text |Cite
|
Sign up to set email alerts
|

Switching CAR T cells on and off: a novel modular platform for retargeting of T cells to AML blasts

Abstract: The adoptive transfer of CD19-specific chimeric antigen receptor engineered T cells (CAR T cells) resulted in encouraging clinical trials in indolent B-cell malignancies. However, they also show the limitations of this fascinating technology: CAR T cells can lead to even life-threatening off-tumor, on-target side effects if CAR T cells crossreact with healthy tissues. Here, we describe a novel modular universal CAR platform technology termed UniCAR that reduces the risk of on-target side effects by a rapid and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
245
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 200 publications
(247 citation statements)
references
References 45 publications
1
245
0
1
Order By: Relevance
“…The specificity of the TM tells such armed UniCAR T cells which cells to attack. Theoretically, the modular UniCAR format has the advantage of an internal self-limiting switch as UniCAR T cells should automatically turn off in the absence of a TM 40 . Therefore, the steerage of such a modular CAR activity should be by far much easier than of a conventional CAR.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The specificity of the TM tells such armed UniCAR T cells which cells to attack. Theoretically, the modular UniCAR format has the advantage of an internal self-limiting switch as UniCAR T cells should automatically turn off in the absence of a TM 40 . Therefore, the steerage of such a modular CAR activity should be by far much easier than of a conventional CAR.…”
Section: Discussionmentioning
confidence: 99%
“…1, we recently described a modular CAR platform termed UniCAR. 40 To redirect UniCAR T cells to target cells TMs are required. On the one hand, TMs bind to the surface of the tumor cell, on the other hand, they form an immune complex with the antibody domain of the UniCAR via a peptide epitope (E5B9) recognized by the UniCAR (Fig.…”
Section: Development Of a Novel Nanobody-based Tm For Retargeting Ofmentioning
confidence: 99%
See 2 more Smart Citations
“…Several approaches are being investigated, including CAR T cells with additional functionality, novel CAR T dosing strategies, and mechanistic studies of observed clinical correlates of safety and efficacy ( Figure 5). For example, results of preclinical studies have demonstrated the viability of various switch mechanisms for CAR T cells [51,[63][64][65]. Switch technology may give clinicians real-time, tunable control of CAR T cell activity and the ability to widen the CAR T therapeutic window.…”
Section: Discussionmentioning
confidence: 99%